Design and realization of a normothermic perfusion system for laboratory tests on pig liver. Issue 1 (January 2020) - Mazzantini, Lucrezia; Dimitri, Mattia; Staderini, Fabio; Cianchi, Fabio; Corvi, Andrea
Ex vivo testing is a fundamental step in the development of new medical devices; indeed without it, it is impossible to proceed with in vivo tests. At the University of Florence, a robotic tool for microwave thermal ablation is under development. Up to now, the thermoablation tests for the validation of the tool were carried out on non-perfused ex vivo livers, providing results that inevitably differ from those obtainable with an in vivo liver. The aim is to design, and consequently create, a compact and transportable system which allows to perfuse a swine liver with physiological solution and heparin. This device should also allow the organ to be transported from the explantation place to the laboratory, keeping it under normothermal condition. The perfusor was designed to simulate the physiological flow within the liver in the most realistic way possible. The design, construction, and optimization of the perfusor have been addressed using the physiological values of hepatic flow and pressure identified in the literature, neglecting in the first instance any load losses. Therefore, open circuit tests were conducted, validated through perfusion tests on freshly explanted pig liver; during these tests, the surface temperature of the organ was recorded using an infrared camera, and the fluid temperature was verified using an immersion probe. The perfusion test showed a good alignment with the open circuit tests, demonstrating the validity of the simplifications adopted to treat the complex vascular structure of the liver.